Magnesium Fertilization Affected Rice Yields in Magnesium Sufficient Soil in Heilongjiang Province, Northeast China - Liu, Zhilei; Huang, Qiuhong; Liu, Xiaohui; Li, Pengfei; Naseer, Muhammad Rehman; Che, Yeqi; Dai, Yaning; Luo, Xiangyu; Liu, Donghui; Song, Lili; Jiang, Baiwen; Peng, Xianlong; et al. (Frontiers in Plant Science, 2021)
Magnesium (Mg) plays a crucial role in rice yield. Heilongjiang Province is the main rice-producing region of China, playing an important role in guaranteeing China’s and the world’s grain security. However, rarely Mg fertilization is applied in this province. Soil Mg status of main rice-producing areas in Heilongjiang Province was investigated and Mg fertilizer experiments were conducted aiming to provide fertilizer recommendation in this region. A total of 358 soil samples from the 0-20 cm and 20-40 cm soil layer from the main rice-producing areas of Heilongjiang Province were collected to analyze soil exchangeable Mg (ex-Mg) and relative chemical properties. Meanwhile, field experiments of soil and foliar Mg application were performed in 2017-2019 to identify the effect of this nutrient on rice yield. The results showed that the ex-Mg concentration in the 0-20 cm and 20-40 cm soil layer was 282 mg kg-1 and 243 mg kg-1, respectively. Moreover, ex-Mg ranged on the abundant and exceptionally abundant level accounted for 75% in 0-20 cm and 55.3% in 20-40 cm. The ex-Mg concentration in the upper soil layer was higher than in the lower soil layer and varied depending on regions, which the west part of Heilongjiang Province showed the highest concentration in both soil layers. Correlation analysis showed that there had a significant (P<0.05) linear relationship between ex-Mg and pH, CEC, ex-K, Ca, K/Mg, and Ca/Mg. Meanwhile, the results of path coefficients demonstrated that pH, CEC, and Ca/Mg had the most direct effect on ex-Mg concentration among these above factors. Soil Mg application had little effect on rice yield, which might be related to the soil Mg concentration and availability, and root uptake activity. Foliar Mg application increased rice yield by 8.45% (P<0.05) compared to without Mg treatment, increased 1000-grain weight by 2.62% (P<0.05), and spikelet number per panicle by 4.19% (P<0.05). In general, the paddy soil ex-Mg concentration in Heilongjiang Province was abundant. Soil-applied Mg played little role in rice yield in ex-Mg abundant regions, while foliar application increased rice yields significantly via increasing 1000-grain weight and spikelet number per panicle.